2014
DOI: 10.1021/np400701k
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Inhibitors from Eurycoma longifolia

Abstract: The roots of Eurycoma longifolia have been used in many countries of Southeast Asia to alleviate various diseases including malaria, dysentery, sexual insufficiency, and rheumatism. Although numerous studies have reported the pharmacological properties of E. longifolia, the mode of action of the anti-inflammatory activity has not been elucidated. Bioguided isolation of NF-κB inhibitors using an NF-κB-driven luciferase reporter gene assay led to the identification of a new quassinoid, eurycomalide C (1), togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
1
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 39 publications
3
81
1
7
Order By: Relevance
“…These apparent contradictory effects of 1 compared to other quassinoids, such as brucein D 25 and quassinoids isolated from Eurycoma longifolia, 26 are very probably dependent upon Mice were pretreated sc with vehicle or 1 (0.5, 1, and 5 mg/ kg) 1 h before intraplantar injection of carrageenan. Three hours after carrageenan injection plantar tissues were collected for quantification of neutrophil migration by MPO activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These apparent contradictory effects of 1 compared to other quassinoids, such as brucein D 25 and quassinoids isolated from Eurycoma longifolia, 26 are very probably dependent upon Mice were pretreated sc with vehicle or 1 (0.5, 1, and 5 mg/ kg) 1 h before intraplantar injection of carrageenan. Three hours after carrageenan injection plantar tissues were collected for quantification of neutrophil migration by MPO activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[27][28][29][30]32 For quassinoids from Eurycoma longifolia, the conclusions were based only on an NF-κB reporter assay after TNF stimulation. 26 Since 1 might not act by blocking transcriptional activity of NF-κB but could instead be inhibiting the production/release of NF-κB-dependent cytokines, the next hypothesis was that 1 activities could likely be mediated by modulation of posttranscriptional mechanisms. To confirm this hypothesis, we used RAW 264.7 cells transfected with the luciferase gene vector controlled by a phosphoglycerate kinase promoter (PKG), a nonviral universal promoter, a region that promotes the recruitment of transcription factors nonspecifically.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However a further study is needed to ensure a structure-activity relationship for the canthin-6-one alkaloids. In a previously study, 9-hydroxycanthin-6-one (4) was reported to inhibit the NF-κB pathway in TNF-a-stimulated HEK-293/NF-kB-luc cells [31]. Among the isolates, sinapaldehyde (9) was found to have the most potent inhibitory effect with an observed IC50 value of 5.92 μM, and erythro-guaiacylglycerol-β-O-4′-coniferyl ether (11) also showed a significant inhibitory effect with an Although 4-hydroxycanthin-6-one (3), 9-hydroxycanthin-6-one (4), 10-hydroxycanthin-6-one (5), and 11-hydroxycanthin-6-one (6) were isolated from the Simaroubaceae family, they have not been reported from A. altissima.…”
Section: Anti-inflammatory Activity Of Isolated Compounds 1-15 From Tmentioning
confidence: 99%
“…NGOC ET AL. (Kuo et al 2003;Park et al 2014;Tran et al 2014). However, E. longifolia roots are harvested after several years of cultivation, i.e.…”
Section: Introductionmentioning
confidence: 99%